Role of Traditional, Complementary, and Integrative Medicine in People with Limb Amputation: A Protocol for a Scoping Review - Kahyun Seo; Yoona Oh; Seon Hee Kim; Na Hyeon Lee; Xiaoyang Hu; Younbyoung Chae; Heeyoung Moon; Kun Hyung Kim (Journal of Acupuncture Research, 2025)
People with limb amputation suffer from pain, psychological symptoms, and longterm disability. Traditional, complementary, and integrative medicine (TCIM) is increasingly being used for various health conditions worldwide. This study aims to identify the types of available evidence in TCIM in people with limb amputation. This scoping review is designed and will be conducted using the framework outlined by Arksey and O’Mally and will be reported comprehensively using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Seven electronic databases and an international trial registry were searched from their inception to September 19, 2023, to identify published, unpublished, or ongoing studies on TCIM for adults who have undergone limb amputations regardless of etiology (i.e., traumatic and nontraumatic). Both controlled and uncontrolled clinical studies will be eligible. The study characteristics, including population, intervention, comparators, outcomes, and other relevant aspects will be descriptively summarized. This review will highlight the current resources and evidence on the role of TCIM in patients who have undergone limb amputation. The findings will be useful for healthcare professionals and researchers to identify research gaps and obtain insights into the role of TCIM in patients who have undergone limb amputation in various settings.